2022
DOI: 10.1021/acsapm.2c01303
|View full text |Cite
|
Sign up to set email alerts
|

Humidity Sensors Based on Magnetic Ionic Liquids Blended in Poly(vinylidene fluoride-co-hexafluoropropylene)

Abstract: Poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) films incorporating 40 wt % of different types of imidazolium ionic liquids (ILs) comprising different magnetic anions (tetrachloroferrate [FeCl 4 ] − , tetrathiocyanatocobaltate [Co(SCN) 4 ] 2− , and tetrachlorocobaltate [CoCl 4 ] 2− ) and imidazolium cation chain lengths (1-butyl-3-methylimidazolium and 1ethyl-3-methylimidazolium) have been developed for humiditysensing applications. The influence of the different ILs on the morphology of the IL/PVD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This interpretation agrees with previously published works. [35][36][37] The presence of PPy is confirmed by the observed absorption bands at 1992, 1530, and 1620 cm −1 (corresponding to C = C and C-C stretching modes of the pyrrole ring), the secondary heterocyclic amine at ≈1275 cm −1 (attributed to the C-N stretching mode of the pyrrole ring), and the breathing C-H bipolaron vibration bands of the pyrrole rings at 1160 and 1022 cm −1 . Peaks below 1000 cm −1 indicate skeletal vibrations of the polymer.…”
Section: Chemical Characterization and Composition Analysismentioning
confidence: 81%
“…This interpretation agrees with previously published works. [35][36][37] The presence of PPy is confirmed by the observed absorption bands at 1992, 1530, and 1620 cm −1 (corresponding to C = C and C-C stretching modes of the pyrrole ring), the secondary heterocyclic amine at ≈1275 cm −1 (attributed to the C-N stretching mode of the pyrrole ring), and the breathing C-H bipolaron vibration bands of the pyrrole rings at 1160 and 1022 cm −1 . Peaks below 1000 cm −1 indicate skeletal vibrations of the polymer.…”
Section: Chemical Characterization and Composition Analysismentioning
confidence: 81%
“…30 The inclusion of hexafluoropropylene (HFP) into PVDF to form the poly-(vinylidene fluoride cohexafluoropropylene) PVDF-HFP structure can improve the hydrophobicity of membrane and lower the crystallinity property. 31 It has been shown that ionic liquids can be used as property control agents for PVDF-HFP membrane, which can affect the morphology, 32 water absorption capacity, 33 and mechanical properties of the membrane. 34 As PVDF-HFP membranes are hydrophobic, the addition of hydrophilic ionic liquids can modulate their hydrophobicity and, thus, impart water responsiveness.…”
Section: Introductionmentioning
confidence: 99%